Supply Chain of Moringa Leaf Products at Banua Zahra Moringa in Palu City: Rantai Pasok Produk Daun Kelor Pada Banua Zahra Kelor di Kota Palu - Masita; Kaseng, Saharuddin; Miru, Sulaeman (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
The purpose of this study was to identify the supply chain model in the moringa product business in Banua Zahra Kelor, Palu City. This research was conducted over one month. The research employed a descriptive qualitative method using a survey approach. The study took place in Palu City, Central Sulawesi Province. Data collection involved interviewing informants who served as sources for this study. Data were analyzed using descriptive methods in NVivo 12, with a focus on supply chain analysis. The results revealed that the Banua Zahra Moringa business has two supply chain models. The first model begins with moringa farmers, followed by Banua Zahra Kelor, and then consumers. The second model starts with moringa farmers, proceeds through Banua Zahra Kelor, then resellers, and finally to consumers.